Estimating emergency department maximum capacity using simulation and data envelopment analysis - Wan Mohd Aminuddin, Wan Malissa; Ismail, Wan Rosmanira; Harunarashid, Husyairi (Indian Society for Education and Environment, 2016)
Recently, the number of Emergency Department visits in UKM Medical Centre has increased rapidly. This has encouraged several healthcare problems occur in the emergency department such as overcrowding. A study was conducted to estimate the maximum possible demand that able to serve by the emergency department with current number of resources. Discrete Event Simulation method was applied to model the Emergency Department system. The model was used to study the behavior of waiting time of the emergency department visits and predict the maximum demand. Finally, combination of Data Envelopment Analysis methods (BCC input-oriented and Super-efficiency-BCC) was used in order to determine the new configuration of number of resources (doctor and nurse) required to maintain their efficient services. Results assume that the Emergency Department capable to accommodate 230 patients per day with an additional doctor to Yellow Zone Treatment Area and new schedule time for Green Zone doctors.